2002
DOI: 10.1093/ps/81.6.793
|View full text |Cite
|
Sign up to set email alerts
|

Dietary arginine intake alters avian leukocyte population distribution during infectious bronchitis challenge

Abstract: Although dietary arginine is a factor in immune function and disease resistance, the full range of effects has yet to be described. In this study, the effects of dietary arginine on leukocyte population changes were examined in the peripheral blood and the respiratory tract of chickens inoculated with infectious bronchitis virus (IBV) strain M41. At 2 wk of age, female line P2a White Leghorn-type chickens were randomly assigned to one of three diets with different arginine levels: a marginally deficient diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
0
29
2
Order By: Relevance
“…Similarly, Fernandes et al (2009) reported that the average live BW of broiler chickens at 42 days was not affected by L-Arg supplementation. Tan et al (2006) also found that supplementing broiler chicken diets with 1.00% L-Arg did not affect the BW gain, whereas Lee et al (2002) showed that increasing the L-Arg level from 100% to 300% NRC (1994) did not affect the BW gain in White Leghorn chickens. D'Amato and Humphrey (2010) reported that the addition of L-Arg at 2 g/kg did not affect the BW, feed intake or FCR compared with chickens fed a basal diet.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Fernandes et al (2009) reported that the average live BW of broiler chickens at 42 days was not affected by L-Arg supplementation. Tan et al (2006) also found that supplementing broiler chicken diets with 1.00% L-Arg did not affect the BW gain, whereas Lee et al (2002) showed that increasing the L-Arg level from 100% to 300% NRC (1994) did not affect the BW gain in White Leghorn chickens. D'Amato and Humphrey (2010) reported that the addition of L-Arg at 2 g/kg did not affect the BW, feed intake or FCR compared with chickens fed a basal diet.…”
Section: Resultsmentioning
confidence: 99%
“…There are several experiments to contradict this, including those of Bhargava et al (1970a and b), Datta et al (1998) and Lee et al (2002). Some authors propose that pathogen challenges always lead to a release of amino acids from body protein stores such as muscle e.g.…”
Section: Partitioning Of Scarce Protein and Energy Resources During Pmentioning
confidence: 99%
“…Lee et al (2002), for example, found that arginine supplementation (a limiting amino acid in birds) improved immune responses in chicks challenged with the infectious bronchitis virus. Low et al (2003) found that mice given a whey protein based diet, which is rich in certain amino acids found in large amounts in immune proteins, had increased antibody responses to several bacterial and viral antigens.…”
Section: Partitioning Of Scarce Protein and Energy Resources During Pmentioning
confidence: 99%
“…This, however, is contradicted by several experiments both in pigs and poultry (e.g. Bhargava et al, 1970a and1970b;Lee et al, 2002) and other species (e.g. Datta et al, 1998), in which additional intake of nutrients above maintenance lead to both increased immune and performance responses.…”
Section: Partitioning Of Scarce Energy and Nutrients Between The Varimentioning
confidence: 95%